Respon Pernapasan Anak dengan Pneumonia yang Mendapatkan Terapi Oksigen - Fredita Andriana Putri; Siti Arifah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to describe the respiratory response in children with pneumonia receiving oxygen therapy. The research method used was a case study of two children, aged 9 and 11 years with pneumonia who received oxygen therapy. Changes in oxygen saturation (SpO₂) and respiratory rate (RR) were observed gradually before therapy, and 1 hour, 2 hours, and 4 hours after administration. The results showed that oxygen therapy improved the respiratory condition of both patients. In patients using nasal cannula (3 L/minute), SpO₂ increased from 93% to 97% within 1 hour and reached 98% at 4 hours, accompanied by a gradual decrease in RR. In patients using NRM (6 L/minute), SpO₂ increased from 89% to 96% within 1 hour and reached 97% at 4 hours, with a more rapid decrease in RR in the initial hours of therapy. In conclusion, there was respiratory improvement after oxygen therapy, with a more rapid response appearing in the early phase of NRM use. Keywords: Nasal Cannula, Non-Rebreathing Mask, Pneumonia, Respiratory Response, Oxygen Therapy